A Comparative Study of Oral Ivermectin and Topical 5% Permethirn Cream in the Treatment of Scabies in Patient Suffering from Diabetes Mellitus (Faridpur Medical College Journal, 2015)
Scabies is one of the commonest diseases among all age groups. Topical permethrin is a widely used treatment option for scabies. Ivermectin is a newer oral agent for the treatment of scabies. This study was done to compare the efficacy of permithrin and oral Ivermectin in the treatment of Scabies in patient suffering from Diabetes mellitus. This comparative clinical trial was carried out in the outpatient department of Dermatology & Venereology, Diabetic Association Medical College Hospital (DAMCH), Faridpur from January 2012 to December 2012. A total 60 cases were enrolled purposively and divided into 2 groups. Group I received 2 doses oral Ivermectin and group II treated with 5% permethirn cream. Patients were followed up at the 3rd and 4th week. Total 86.6% patients of Ivermectin group and 90% of permethrin group were cured. Though permethrin showed somewhat more effective, the difference was not statistically significant. The study found that both ivermectin and permethrin were similarly effective in the treatment of scabies in patients suffering from Diabetes Mellitus.Faridpur Med. Coll. J. 2014;9(2): 70-72